Water, soil and resilience: a roadmap for enhancing agricultural outcomes in Egypt’s saline environments - Lahham, N.; Amer, K.; Abd El-Dayem, M. S.; Abdel-Azim, R.; Gaafar, I.; El-Shirbeny, M.; Mohamed, E.-S. S.; Yassin, D.; Khalifa, M.; Brouziyne, Youssef; Al-Zu’bi, Maha; Tawfik, Mohamed (International Water Management Institute, 2025)
Water, Soil and Resilience presents an integrated, water-centered approach to strengthening agricultural resilience and food security in the face of climate change, land degradation, and growing water scarcity. Drawing on CGIAR and partner research, the report highlights how pressures on water and soil systems—when combined with climate variability and governance challenges—are undermining agricultural productivity and rural livelihoods, particularly in water-stressed and fragile contexts.